The mediating effect of intention to repeat the visit to a port of call between city evaluation and satisfaction with the visit - Santos, M-C.; Trindade, G. (ATMC 2019 - “MARKETING FOR MORE SUSTAINABLE AND COLLABORATIVE TOURISM”., 2019)
Abstract On the recent economic crisis cruise tourism showed resilience, becoming the fastest growing segment in travel. The globalization of cruise industry affects the host ports significantly. Passengers of diverse nationalities experience a full service offer, while on board or onshore: hospitality, entertainment and cultural tours. From the cruise company’s perspective, land attractions and infrastructure are crucial itinerary factors. This study analyzes the destination role to the cruise choice, through a survey applied in 2017 and in 2018 to over two thousand cruisers of 80 docked ships in Lisbon. Results show that the probability to visit again the city in a cruise trip is a mediating variable between the two dimensions of the evaluations of the city offer and the satisfaction with the visit, which deep the understanding of the city offer with the satisfaction with the visit.